Frogs and toads. - Turner, Edward frey50 (Raintree Editions. Milwaukee, 1974)
Discusses the characteristics and behavior of frogs and toads, their relationship to man, and their suitability as pets.
Bibliography
Keywords: Frogs -- Juvenile literature; Toads -- Juvenile literature; Frogs; Toads